Truly, madly, sheeply - Frederick, Heather Vogel (Frederick, Heather Vogel. Pumpkin Falls mystery, 2023)
"The Pumpkin Falls Private Eyes face a pumpkin snatcher and a haunted farm in the fourth cozy mystery of the Edgar Award-nominated middle grade series from the author of the beloved Mother-Daughter Book Club books. It's autumn in New England and Truly and her fellow Pumpkin Falls Private Eyes are gearing up for the annual Halloween Festival. Aunt True and her new husband, Rusty, have bought Ethel and Elmer Farnsworth's dilapidated old farm on the edge of town, where they're going to raise sheep. Truly and her grandparents have volunteered to farm- and sheep-sit while the newlyweds are on their honeymoon. But as always, the small town of Pumpkin Falls is soon confronted with a mystery-the highly decorated pumpkins outside the shops in town have gone missing! In broad daylight! And soon after, someone or something, is trying to get Aunt True and Rusty to leave their new property with some seriously spooky hauntings. With the arrival of a new heartthrob student from Italy, Emilio, and sweet Calhoun still in the picture, Truly has her hands full and will need all of her Private Eyes to help her uncover the shenanigans this fall season" --